Some Molecular Adducts of (C6H5CH2)2Te and (C6H4)2 with Monodentate Ligands - Srivastava, Shekhar; Singh, Deepa (Asian Journal of Chemistry, 2010)
Twenty molecular adducts of the type RR´Te.L (where R= R´ = C6H5CH2, RR´ = (C6H4)2 and L = monodentate ligands) have been synthesised and their structures were determined by various physico-chemical techniques, i.e., elemental analysis, molar conductivity, and X-ray photoelectron spectra.